2017
DOI: 10.1016/j.ejvs.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative Simulation of the Appropriate C-arm Position Using Computed Tomography Post-processing Software Reduces Radiation and Contrast Medium Exposure During EVAR Procedures

Abstract: Pre-operative simulation of the appropriate C-arm angulation in two dimensions using dedicated computed tomography angiography post-processing software is feasible and significantly reduces radiation and contrast medium exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Typical projection angles to visualize iliac bifurcations range from 20° to 60° 5 (Table 1), which frequently are geometrically impossible to reach, and even if achieved, it implies a decrease in image quality and increase in the scatter radiation. FORS technology works independently of these geometric restrictions and can display any projection without adding any radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Typical projection angles to visualize iliac bifurcations range from 20° to 60° 5 (Table 1), which frequently are geometrically impossible to reach, and even if achieved, it implies a decrease in image quality and increase in the scatter radiation. FORS technology works independently of these geometric restrictions and can display any projection without adding any radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the anatomy of the iliac bifurcation is assessed with roadmaps using 20 to 30 contralateral anterior oblique projection, in order to separate the internal from external iliac artery. 18 Stahlberg et al 19 reported in a recent study that calculation of an appropriate C-arm position based on preoperative CTA can significantly decrease the number of digital subtraction angiograms needed for successful visualization of the iliac bifurcations, thus reducing radiation and contrast dose.…”
Section: Discussionmentioning
confidence: 99%
“…18 Stahlberg et al. 19 reported in a recent study that calculation of an appropriate C-arm position based on preoperative CTA can significantly decrease the number of digital subtraction angiograms needed for successful visualization of the iliac bifurcations, thus reducing radiation and contrast dose.…”
Section: Discussionmentioning
confidence: 99%
“…der supra-und infrarenalen Angulation) exakt beurteilt werden. Ferner lassen sich die geeigneten C-Arm-Angulationen berechnen, die während einer endovaskulären Therapie dazu beitragen können, die Strahlen-und Kontrastmittelexposition zu senken [27].…”
Section: Monatenunclassified